Operation of photosynthetic apparatus of citrus leaves in winter and spring - ZENG Guang-hui; GUO Yan-ping; WANG Fa-ge; WU Zhen-wang (浙江大学学报. 农业与生命科学版)
Optimum temperature for photosynthesis of citrus leaves planted in field was lower in winter than in spring, and it was higher than environmental temperature in winter. In the winter, the net photosynthetic rate (Pn), Rubisco activity, rate of RuBP regeneration, apparent quanturn yield (AQY), photochemical efficiency of PS Ⅱ (Fv/Fm), photochemical efficiency under light (Fv′/Fm′), photochemical quenching coefficient (qP), and electron transport rate (ETR) were lower, but the ratio of internal CO2 concentration (Ci) to air CO2 concentration (Ca), and non-photochemical quenching coefficient (qN) were higher, PSⅡ reaction centers were reversibly inactivated or damaged. These results indicated that the optimum temperature for photosynthesis of citrus leaves was adaptable to the changing natural environmental temperature. Low temperature in winter limited photosynthetic carbohydrate metabolism and photochemical reaction caused low photosynthesis.